AS/RS Technology Selection Using Spherical Fuzzy TOPSIS and Neutrosophic TOPSIS - Boltürk, Eda (Springer International Publishing, 2019)
Spherical Fuzzy sets (SFSs) are proposed by Kutlu Gundogdu and Kahraman [1] and neutrosophic sets (NSs) are introduced by Smarandache [2]. TOPSIS is a multi-criteria decision-making method (MCDM) and it is a combination method. In this paper, we applied SFSs TOPSIS and NSs TOPSIS and we compare the results of each other. The methods are applied to an Automated Storage and Retrieval Systems technology selection problem and future suggestions are given in result.